A study of cardiac changes in asymptomatic diabetic patients in comparison with normal population - Bendigeri, Mukhtarahmed; Sadique, Rizwan P.; Aziz, Asbin Abdul; Jaladhar, Prakruthi (International Journal of Advances in Medicine, 2019)
Background: India is predicted to bear the greatest Coronary artery disease (CAD) burden, according to the estimates from the global burden of disease study. Majority of the time the patient of diabetes presents with complications like Myocardial infarction (MI), heart failure, being end stages of cardiovascular disease associated with other macro and micro-vascular complications. Methods: This study was done in view of screening the asymptomatic diabetic individuals presenting to our hospital for any evidence of early cardio-vascular manifestations. With the aid of non-invasive testing such as electrocardiography (ECG) and 2D echo the early changes were noted and compared with the normal population and the cardiac status thus evaluated. A total of 106 patients (53 were diabetic and 53 non-diabetic controls) were included in the study in order to compare the ECG and 2D echo findings among the population. The main aim of the present study was to observe the ECG manifestations in diabetic patients without overt symptoms of any cardiac disease and to evaluate the ECG changes along with 2D echocardiogram in asymptomatic diabetic patients and compare with normal population. Results: From the study, it was observed that majority among the diabetic population were found to have statistically significant changes in the ECG like PR interval prolongation, T wave inversions and QT interval prolongation. 2D ECHO studied showed the presence of Left ventricular diastolic dysfunction and Regional wall motion abnormalities to be evident among the diabetic population. Conclusions: It was concluded from the study that diabetic patients have a higher risk of cardiovascular morbidities compared to the general population and ECG changes are observed even when they are clinically asymptomatic. This observation has been confirmed by the 2D echo findings. It is essential to screen diabetic patients at an early stage to prevent cardiovascular complications. ECG being a relatively cheap and non-invasive investigation should be utilized to screen diabetics for the same.